Pengaruh Modal Sendiri, Volume Usaha dan Total Aset terhadap SHU Koperasi Simpan Pinjam di Tanjungpinang - Rikayana, Hadli Lidya; Suryani, Ari; Haryadi, Teddy (SAFE-Network, 2023)
This research aims to determine the influence of own capital, business volume and total assets on the Sisa Hasil Usaha (SHU) of Savings and Loans Cooperatives in Tanjungpinang City. This research uses descriptive research with a quantitative approach and the data used is secondary data which includes independent variables, namely own capital, business volume and total assets. Secondary data in this research was obtained from cooperative financial reports. The data analysis method in this research uses descriptive statistical test methods, classical assumption tests and multiple regression analysis. Partially, own capital, business volume and total assets have an influence on the remaining business results in cooperative savings and loan business units in Tanjungpinang City. Own capital, business volume and total assets together have an influence on the remaining business results in the cooperative savings and loan business unit in Tanjungpinang City with an R2 value of 88.1%. This means that 88.1% of SHU is influenced by own capital, business volume and total assets and the remaining 21.9% is influenced by other factors.